ITF Transport Outlook 2013. Funding transport. - (:unkn) unknown (My University, 2013)
The ITF Transport Outlook 2013 presents and discusses global scenarios concerning the development of transport volumes through 2050. The analysis highlights the impact of alternative economic growth scenarios on passenger and freight flows and the consequences of rapid urbanisation outside the OECD.
Keywords: Verkehr; Verkehrswesen; Verkehrsstatistik; Finanzierung